CAL - ANTENNAS COMPUTER-AIDED LEARNING OF ANTENNAS - `TONYE, Emmanuel (Applied Computational Electromagnetics Society Journal (ACES), 2022)
CAL-ANTENNAS is a tool containing graphics ( 2D and 3D) and sounds coded in the Turbo Pascal 5.5 language, for the implementation of educational software on antennas. From the Units files, a data base (frequency bands, antenna forms, antenna dimensions, formulae, characterising radiation) and a repertory of numericals methods (integration, graphs plotting, etc...) have been developped, complying with speed contraints. The necessary fundamental principles are contained in text files. Thus, this is one of the first structured software packages developed on the computer in the domain of antennas that treats the fundamental principles and the methodology of design. This version of CAL-ANTENNAS for the microcomputer based on the Intel 386 and 486 Microprocessors contains more than a hundred illustrations. [Vol. 8, No. 1, (1993), Special Issue on Computer Applications in Electromagnetics Education, pp 138-156]